2015
DOI: 10.1155/2015/379451
|View full text |Cite
|
Sign up to set email alerts
|

Simplified Tai Chi Resistance Training versus Traditional Tai Chi in Slowing Bone Loss in Postmenopausal Women

Abstract: Background. This study examined whether simplified Tai Chi resistance training is superior to traditional Tai Chi in slowing bone loss in postmenopausal women. Methods. This prospective trial included 119 postmenopausal women (age: 52–65 years). Subjects were randomly assigned to participate in a traditional Tai Chi program (TTC, n = 40), a simplified Tai Chi resistance training program (TCRT, n = 40), or a blank control group (routine activity, n = 39). The TTC involved traditional Yang Style Tai Chi. The pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 22 publications
1
42
0
1
Order By: Relevance
“…The simplified Tai Chi exercise not only keeps the original essence of the traditional Tai Chi improving physical function, but also is more easily accessible to older adults [16]. The resistance training in the simplified Tai Chi exercise has been proven to have a positive impact on alleviating bone mass loss [16]. The present study also showed that the simplified Tai Chi improved the FMS scores, which may be attributed to its main function improving physical function.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The simplified Tai Chi exercise not only keeps the original essence of the traditional Tai Chi improving physical function, but also is more easily accessible to older adults [16]. The resistance training in the simplified Tai Chi exercise has been proven to have a positive impact on alleviating bone mass loss [16]. The present study also showed that the simplified Tai Chi improved the FMS scores, which may be attributed to its main function improving physical function.…”
Section: Discussionmentioning
confidence: 52%
“…Physical exercise has been proven to improve muscular strength and balance ability for fall prevention in older adults [14, 15]. Tai Chi is a safe, health-enhancing exercise and is suitable for older adults due to the features of gentleness and softness [16]. Tai Chi has been extensively studied and its positive impact includes improving postural stability and alleviating degeneration of muscular strength in older adults [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of included studies (44 trials) had a moderate quality [8,10,11,14,26,28,30,[32][33][34][35] [35,65,88,89], whilst two studies prescribed jumping [25,84] and four groups performed non-WB + RT [29,60,71,80]. There was a significant increase in BMD favouring exercise interventions over control groups (P < 0.001, SMD = 0.37, 95%-CI: 0.25-0.50), with a substantial level of heterogeneity between trials (I 2 =73.2 %, Q = 262.43, degrees of freedom (df)=78, P < 0.001; ▶Figure 1).…”
Section: Methodological Qualitymentioning
confidence: 99%
“…No significant differences were observed between subgroups (P = 0.36). Significant effects were demonstrated for Jumping + RT + WB (SMD = 0.71, 95%-CI: [8, 10, 23, 26, 30, 34, 37-39, 45, 47, 53, 63, 66, 68, 74, 76, 86, 92, 93], 15 WB-AE [13,14,32,33,44,49,60,61,64,73,77,81,82,85,92], 15 DRT [11,12,27,36,41,43,50,59,72,75,78,79]; eight Jumping + RT + WB [8,24,42,55,57,62,70], four non-WB + RT [29,60,71,80], four Tai Chi [35,65,88], and two Jumping [24,84]. A significant increase in BMD of exercise compared to control group (P < 0.0001, SMD = 0.33, 95%-CI: 0.23-0.43) was observed, with a moderate level of heterogeneity (I 2 =59.8 %, Q = 166.35, df = 67, P < 0.001; Fig.…”
Section: Methodological Qualitymentioning
confidence: 99%